HUMAN CAPITAL AND URBAN GROWTH IN ITALY, 1981–2001. Issue 1 (10th September 2019) - Giffoni, Francesco; Gomellini, Matteo; Pellegrino, Dario
Abstract : Over the last decades of the XX century, human capital has emerged as a critical source of agglomeration economies fueling urban growth in advanced economies. Focusing on the Italian case, this paper assesses the contribution of human capital to urban growth, the latter gauged by employment growth between 1981 and 2001. A 10% higher share of college‐educated residents prompted a higher growth in employment in the 0.5–2.2% range. These results hold controlling for a wide set of urban characteristics and using an instrumental variable approach. By exploiting a spatial localization model, we disentangle the estimated effect into two components related to higher productivity and to higher life quality, respectively. We found that the former contributed to more than 60% of the effect at municipal level, and to over 90% at the wider local labor market level.